Model Komunikasi dan Informasi Terpadu dalam Pengelolaan Bencana di Kabupaten Karo Berbasis Web - Puji Lestari; Eko Teguh Paripurno; Hikmat Surbakti; Dikau Mahardika Pratama (Program Studi Ilmu Komunikasi, 2021)
The people of Karo Regency are suing the Karo Regional Government (Pemda) for not providing an integrated communication and information system in the management of the Mount Sinabungdisaster. The purpose of this study was to find an integrated model of communication and information in disaster management in Karo Regency. This research uses a qualitative approach with a single instrumental case study method to solve the problem of demands in theKaro community by finding a new model of disaster communication through website implementation. The object of research is a model of integrated communication and information. The subjects of this study were the Head of the Regional Disaster Management Agency (BPBD) and the team, the Head of the Communications and Informatics Service and the team. Data collection techniques through in-depth interviews, observation, and Focus Group Discussion (FGD). Data analysis techniques are carried out by displaying data, reducing relevant data, making interpretations, and concluding research results. The results of this study found an integrated model of communication and information in disaster management in Karo Regency. This research contributes in the form of recommendations for integrated communication and information models in disaster management in Karo Regency through the website. The new findings theoretically add critical thinking elements in the Source-Message-Channel-Receiver-Effective Theory to deal with disaster problems.Keywords: Critical Thinking, Disaster Communication, Integrated Communication Model, Mount Sinabung.